2017
DOI: 10.1186/s12903-017-0450-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum zinc levels in patients with recurrent aphthous stomatitis (RAS)

Abstract: BackgroundRecurrent aphthous stomatitis (RAS) is an ulcerative disease of the oral mucosa without a clearly defined etiology. The aim of the study was to evaluate the serum zinc levels in patients with RAS in comparison to healthy controls and to validate the association between zinc levels and the course of RAS.MethodsSeventy-five patients with RAS and 72 controls underwent full dental examination. Serum zinc levels were determined by flame atomic absorption spectroscopy (F AAS). The results were statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Serum zinc concentration indicates recent consumption of zinc or regular zinc intake, indicating that, in populations with low zinc diet, the serum zinc level is lower, which shows a high zinc deficiency risk. These studies showed that, the best time to measure serum zinc is whilst fasting in morning [ 23 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum zinc concentration indicates recent consumption of zinc or regular zinc intake, indicating that, in populations with low zinc diet, the serum zinc level is lower, which shows a high zinc deficiency risk. These studies showed that, the best time to measure serum zinc is whilst fasting in morning [ 23 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals suffering from other mucosal disease such as oral lichen planus, recurrent aphthous stomatitis, xerostomia and burning mouth syndrome have also been recognized as having lower serum zin concentrations compared to healthy individuals [ 28 , 33 ]. In the case of other viral diseases and body minerals, in a study conducted by Okwara et al [ 34 ], 51 adult patients with human immunodeficiency viral infection (HIV) and 48 healthy people were included.…”
Section: Discussionmentioning
confidence: 99%
“…Other agents like zinc supplements have also been reported in the recovery of aphthous ulcers [10]. However, based on several clinical trials, it seems that systemic zinc supplement therapy in RAS is still a matter of debate [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that the best time to measure serum zinc was whilst fasting in morning. (17,23) In another article, published by Femiano et al in 2005, they examined the effect of zinc on RHL. In this paper, 20 patients (including 12 women and 8 men) with an average age of 26.6 with a history of RHL more than 6 times per year and a recovery period of more than 8-14 days were treated with zinc sulfate 22.5 mg twice daily for 4 months.…”
Section: Discussionmentioning
confidence: 99%